Thailand : adjusting to success : current policy issues - Robinson, David, 1958-; Byeon, Yangho, 1954-; Teja, Ranjit, 1958-; Ohio Library and Information Network (Washington, D.C. : International Monetary Fund, 1991)
Thailand's sucess with economic development in recent decades is due mainly to is commitment to an outward-looking, market-based economy, a development strategy centered on the private sector, and cautious financial policies. This papers dicusses recent economic strains and how the authorities are coping with them to sustain the momentum of development
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
English
Keywords: Fiscal policy; Finance; Finance -- Thailand; Fiscal policy -- Thailand; Thailand -- Commercial policy; Thailand -- Economic policy